PI(4,5)P(2)-dependent regulation of exocytosis by amisyn, the vertebrate-specific competitor of synaptobrevin 2 - Kondratiuk, Ilona (Proc Natl Acad Sci U S A, 2020)
The functions of nervous and neuroendocrine systems rely on fast and tightly regulated release of neurotransmitters stored in secretory vesicles through SNARE-mediated exocytosis. Few proteins, including tomosyn (STXBP5) and amisyn (STXBP6), were proposed to negatively regulate exocytosis. Little is known about amisyn, a 24-kDa brain-enriched protein with a SNARE motif. We report here that full-length amisyn forms a stable SNARE complex with syntaxin-1 and SNAP-25 through its C-terminal SNARE motif and competes with synaptobrevin-2/VAMP2 for the SNARE-complex assembly. Furthermore, amisyn contains an N-terminal pleckstrin homology domain that mediates its transient association with the plasma membrane of neurosecretory cells by binding to phospholipid PI(4,5)P(2). However, unlike synaptrobrevin-2, the SNARE motif of amisyn is not sufficient to account for the role of amisyn in exocytosis: Both the pleckstrin homology domain and the SNARE motif are needed for its inhibitory function. Mechanistically, amisyn interferes with the priming of secretory vesicles and the sizes of releasable vesicle pools, but not vesicle fusion properties. Our biochemical and functional analyses of this vertebrate-specific protein unveil key aspects of negative regulation of exocytosis.